KEMAMPUAN LITERASI NUMERASI SISWA SD INKLUSIF DALAM MEMECAHKAN SOAL CERITA - Ermiana, Ida; Umar, Umar; Khair, Baiq Niswatul; Fauzi, Asri; Sari, Mega Puspita (COLLASE (Creative of Learning Students Elementary Education), 2021)
This study aims to describe the numeracy literacy ability of inclusive students in solving story problems. This type of research is descriptive qualitative research. The subjects of this study were inclusive students at Madrasah Ibtidaiyah Darul Hikmah who were in high class as many as 2 students. Data collection techniques used in this research are technical tests and non-tests. The test technique uses an instrument of description questions to see the numeracy literacy abilities of inclusive students in the form of story questions about simple arithmetic operations. Then the non-test technique used interviews with inclusive teachers and students who were used as research subjects. The data analysis technique uses triangulation techniques, namely the stages of data reduction, data presentation, and conclusion drawing. The results of this study indicate that the numeracy literacy ability of inclusive students is still said to be below. Subject A's responses to the questions are 1) subject A can use contextual understanding to solve mathematical problems but is still not correct in solving them; 2) unable to write the conclusion of the settlement, and 3) subject A has not been able to relate various representations when solving problems. Meanwhile, subject B's response to the question is: 1) can write the process in reaching a solution, but it is not complete and not correct; 2) have also been able to write the conclusions of mathematical results based on the results obtained based on the written completion process but the answers given are not correct, and 3) have been able to use contextual understanding to solve mathematical problems but it is not correct.